LEGAL BASIS OF THE MECHANISM OF ACTIVITY OF THE UZBEK STOCK EXCHANGE - Umaraliyevich, Mexmonov Sultonali; Saliyevna, Jamaldinova Asalxon; qizi, G'aybullayeva Zilola Raxmatullo; og'li, Habibulloh Ravshan (International Journal of Psychosocial Rehabilitation, 2020)
Abstract: The article analyzes the legal bases of the stock exchange’s activity in Uzbekistan, the system of securities trading in the stock exchange system, its functioning, improvement, and the development of exchange trading systems.